The Effect of Hydraulic-Natural Fracture Networks on the Waterflooding Development in a Multilayer Tight Reservoir: Case Study. (21st January 2021) - Hui, Gang; Chen, Shengnan; Wang, Youjing; Gu, Fei
Abstract : An integrated hydraulic fracturing followed by waterflooding was conducted in a heterogeneous sandstone formation in the Northern Shanxi Slop of Ordos Basin in Western China. Water breakthrough quickly occurred, and the underlying mechanism of water breakthrough has not been well understood. Such mechanism needs to be investigated comprehensively from the spatial connectivity of multilayer sand bodies and characterization of hydraulic-natural fracture networks. Here, an integrated approach is proposed to tap the remaining oil in the individual sand layer during the late-stage development of tight sandstone reservoirs. A case study is utilized to demonstrate the applicability of the integrated method. It is found that the six sand layers could be further divided within the target oil layers. These sand layers have a variety of physical and mechanical properties, leading to the asymmetric spatial distribution of hydraulic fractures after performing the integrated fracturing of whole oil layers. The spatial difference of sand bodies conforms to the features of the multiperiod superimposed channel in the sedimentary environment of fan delta front. The natural fractures were generated from the tectonic movement in the Mesozoic period with a dominant orientation of approximately NE 67°. The asymmetric hydraulic fractures propagated and connected with the preexisting natural fractures, forming the intricate natural-hydraulic fracture networks. The water breakthrough pattern in each sand layer is primarily ascribed to the spatial distribution of the hydraulic-natural fracture networks and sedimentary microfacies. The refracturing operations based on the remaining oil distribution in sand layers are proven to be effective in further developing the formation. The average oil production of related wells increased from 0.61 t/d to 2.18 t/d. This practical development strategy provides insights for further development of likewise heterogeneous tight sandstone reservoirs.